Driving force heterogeneity of urban PM2.5 pollution: Evidence from the Yangtze River Delta, China. (June 2020) - Wang, Sufeng; Xu, Ling; Ge, Shijian; Jiao, Jianling; Pan, Banglong; Shu, Ying
Graphical abstract: Highlights: Determinants of PM2.5 in prefecture-level cities were given by Quantile regression. Population size and population quality significantly reduced the PM2.5 pollution. Environmental policies should focus on different factors under different quantiles. Abstract: As one of the largest metropolitan regions in the world and the most dynamic urban agglomeration in China, the air pollution in the Yangtze River Delta (YRD) is attracting attentions. This paper examined the driving factors of PM2.5 pollution of 26 prefecture-level cities in the YRD from 2006 to 2016, based on the perspective of population development and its three factors: population size, population quality, and population structure. The quantile regression model was applied to systematically investigate the heterogeneity of the causes of urban PM2.5 pollution under different quantile levels. The empirical results showed that the increase of urbanization rate (a representative indicator of population size) and the urban disposable income per capita (a representative indicator of population quality) significantly reduced the PM2.5 pollution. The PM2.5 emissions increased correspondingly with the expansion of population structure indicators. Moreover, the effects of population development on the PM2.5 pollution in YRD cities had both homogeneity and heterogeneity. The homogeneity was supported by the fact that the impacts of most population variables decreased with increasing quantile level. This indicated that the PM2.5 pollution was more sensitive to population development when the pollution level was low. The heterogeneity relied on two aspects: firstly, the key driving factors of PM2.5 pollution differed in cities with same pollution level; secondly, with increasing pollution levels, the impacts of different population development factors on PM2.5 pollution presented different trends. Policy recommendations from the perspective of population development are provided for prefecture-level cities to control PM2.5 pollution.